Upper Respiratory Infections among Under-Five Age Group Children at Urban Slum, Islamabad - Mahwish Akhtar Qureshi, Maliha Akhtar Qureshi, Muhammad Mutassim Ismail, Sobia Aamir, Rida Ajmal Khan, Mehwish Rana (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of this study was to identify the prevalence of Upper respiratory infection (URIs) in children less than five years of age. Methodology: This cross-sectional study was carried, in 360 children living in 115 houses of urban community of several socio -economic settings at, Burma Town, Tarlai Kalan, an Urban slum, in Islamabad. 110 children under 5 years were found with URIs out of a total of 360 children. A Questionnaire about Socio-demographic distribution of the sample population having, information of their parents, housing conditions, type of using cooking fuel, and general clinical examination was done. Results: 41.9% of the 110 children were 0 to 1 years old, 45.36% were 1 to 4 years old, and 12.96% were 4 to 5 years old. The gender distribution was 48 % girls and 62 % boys. About 40% children looked malnourished. According to symptoms, about 82% of children were having cough, 75% nasal discharge, 32% fever, 3% with fast breathing. Conclusion: In this study, it was observed that all children were having cough, nasal discharge, fever, sour throat, muscle aches, causing in severity of URI. Keywords: Children, Upper respiratory infections, Socioeconomic & Environmental risk factors, Burden of disease, Incidence, Awareness.